Negotiating identity using Bicultural Identity Integration Model : the Bawean in Malay construct - Muhammad Ridhwan Sarifin,; Mohamad Fauzi Sukimi,; Azlina Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article aims to show the negotiation process in constructing Bawean ethnic identities as part of Malay sub-ethnic in Malaysia. This study used the Bicultural Identity Integration Scale-2 (BIIS-2). In-depth interviews were used to achieve all of the objectives of this study. This article focused only on the outcome of bicultural identity integration, namely the level of ethnic identity trends and how Bawean negotiates with other Malay cultures. Five findings were identified. First, the results of the analysis revealed that the majority of informants see themselves as Malays due to their religion which is Islam where they know how to act as Malaysian citizens. Second, the majority of informants do not feel entrapped between Bawean and Malay culture because of the willingness of Bawean people to deal with cultural diversity. Third, there are many cultural similarities which make the majority of the informants feel they have no conflict about having two cultures. Fourth, it is surprising that the majority of informants have low self-Malay feelings because of the very strong bond within the ethnic group itself. Finally, the fact that there is a positive need for each other about culture explains why the majority of informants did not abandon Bawean culture for Malay culture. The results of this study showed that informants are able to respond to the development of nation-state processes in a national context. The identity of Bawean people which is one of the sub-ethnic categories in Malay is still at a good level and can be enhanced since they are believers of Islam which is compulsory for them to be categorised as Malay. This clearly shows their effort to integrate with Malay people.